Optimization of Co-Flow Jet Parameters for Ahmed Body Application - Derghal, Ikram; Saifuddin, Mohd; Mohd Noh, Mohd Hafiz; Abdul Hamid, Ahmad Hussein (International Journal of Integrated Engineering, 2023)
This study evaluates the drag reduction strategy of suction and blowing on idealize automotive vehicle, Ahmed Body. Optimization approach is adapted in order to analyse the effect of slot location, momentum coefficient and slot angle on the vehicle which experiencing drag. Despite all the efforts that have been done to reduce the Ahmed body drag using various active flow control system, most of the drag reduction were only less than 15%. A 25° Ahmed body with build in co-flow jet is modelled using a CAD software. The flow around the Ahmed body is simulated at Reynolds number based on length Re = 4.29 × 106. The governing equation were solve using an open source software package, which has been validated against experimental data. Pressure Implicit with Splitting of Operator (PISO) algorithm is applied to solve the equation. The outcome of the simulation are varies depending on the variables. Some show a decrease in drag while there are also that actually increase the drag of the system. This are caused by the suction and blowing slots that effect the surrounding air flow whether it is reducing or increasing the wake size downstream of the body. The result shows the momentum coefficient and location of both suction and blowing jet played an important role of manipulating the flow around the body and reducing the drag. The velocity contours indicated that the key to drag reduction is by using 40 m/s jet velocity, placement of suction and blowing away from each other.